Effect of dietary supplementation of different strains of Streptococcus lactis on the biological performance of broilers - BHATT, R S; KATOCH, B S; DOGRA, K K; GUPTA, R; SHARMA, K S; SHARMA, C R (The Indian Journal of Animal Sciences, 2013)
The dietary supplementations (6.9 x 108 celll/kg feed) of 4 strains (3 from HPK V. Pal am pur and 1 from CFTRI. Mysore) of Streptococcus lactis were undertaken to study the biological performance of Starbro broilers up to 6 weeks of age. SI strain procured from the CFTRI, Mysore, was the most effective because it showed significantly (P<0.05) higher broiler. live-weight gain coupled with efficient feed efficiency ratio, and minimum chick mortality during both starter and finisher phases. There were also nonsignificant variations in dressing percentage, duodenal pH and duodenal thickness with this strain as compared to other treatments including control.